Refinement of component model standards and conventions - Aris H.; Salim S.S. (2023)
One the research areas in component-oriented software development is component model development. Various component models have been defined and specified, but whether or not they meet the purpose of a component model is still a subject of discussion. This paper presents our effort in refining the standards and conventions of a component model in order to produce components that meet their purpose. Application of the refined standards and conventions to a selection of component models is also presented. 2008 Springer-Verlag Berlin Heidelberg.